URDU-SIGNIFICANCE OF CORANICA AMONG THE WESTERN QURANIC PROJECTS: AN ANALYTICAL STUDY - Dr Muhammad Samiullah (دی اسکالر)
To date, knowledge of the textual history of the Qur'an has relied primarily on the Arabo-Islamic tradition. The study of material evidence, which should contribute to understanding the historical development of the canonization of the text, form the first part of the Coranica project. The Coranica project gives priority to an empirical approach, contributing to the history of the Qur'anic text based primarily on material evidence, distributed chronologically, and less on the data of the Arabo-Islamic tradition. As part of its empirical approach, Coranica aims to take into account current developments and the latest discoveries. These include continuing and amplifying the research on older written witnesses of the Qur'an, a field of study that lay dormant until the 1980s and was revived by the discoveries of Sanaa, and other well known collections, such as those of St. Petersburg or Istanbul. Coranica provides a platform for cooperation between those in the fields of antiquity and Islamic studies. The project brings together researchers from various disciplines from Germany, France, England, Austria and Italy. Coranica began in 2011, and is directed by Christian Robin and François Deroche (AIBL, Paris) and Michael Marx and Angelika Neuwirth (BBAW, Berlin). In this paper, the introduction and the details of the project are given for the urdu-natives with critical analysis of the project components theoretically.